Menembah gusti sebagai basis adab menuntut ilmu - Firmansyah, Nanda Iqbal; Mulawarman, Aji Dedi (Oetoesan-Hindia: Telaah Pemikiran Kebangsaan, 2020)
This study aims to explore the understanding and experience of awareness about the study manners of accounting students of Universitas Brawijaya based on the concept of menembah Gusti (worshipping God) according to the thinking of HOS Tjokroaminoto, as an important part of the practical objectives of accounting education. The research method used in the research is Hyper-Postphenomenology and the objects were students who have taken the Professional Business Ethics course. The results showed that all informants had a conceptual understanding of the importance of menembah Gusti which was represented by manners (adab) before science. Different results can be seen at the awareness implementation stage with regard to worshipping God which is represented through adab before science, manners in knowledge, and manners in all activities. Only one informant has an implementative awareness regarding manners. Abstrak Penelitian ini bertujuan untuk mengetahui pemahaman dan pengalaman berkesadaran mengenai adab menuntut ilmu mahasiswa akuntansi Universitas Brawijaya berbasis konsep menembah Gusti menurut pemikiran HOS Tjokroaminoto, sebagai bagian penting dari praksis tujuan pendidikan akuntansi.Metode penelitian yang digunakan dalam penelitian adalahHyper-Postphenomenologypada mahasiswa akuntansi yang telah menempuh mata kuliah Etika Bisnis Profesi. Hasil penelitian menunjukkan bahwa semua informan memiliki pemahaman konseptual mengenai pentingnya menembah Gusti yang direpresentasikan melalui adab sebelum ilmu. Hasil yang berbeda terlihat pada tahapan implementasi berkesadaran berkenaan menembah Gusti yang direpresentasikan melalui adab sebelum ilmu, adab dalam berilmu, dan adab di seluruh aktivitas. Hanya satu informan yang telah memiliki kesadaran implementatif berkenaan dengan adab.